Talking Trials: An arts‐based exploration of attitudes to clinical trials amongst minority ethnic members of the South Riverside Community of Cardiff - Sarah Bridges; Catherine Lamont‐Robinson; Allan Herbert; Mashmooma Din; Carl Smith; Nasra Ahmed; Arafa Ali; Sudipta Bandyopadhyay; Saleema Bibi; Rossana Canu; Mariama N. G. Correia; Mamadu S. Djalo; et al. (Wiley, 2023)
Abstract Introduction Clinical trials must include diverse participants to ensure the wide applicability of results. However, people from ethnic minorities are included in clinical trials at rates lower than expected given their share of the population. Working with South Riverside Community Development Centre (SRCDC), Talking Trials used public engagement to foster discussions around the underrepresentation of those from minority ethnic communities in clinical trials and to identify and address concerns surrounding trial participation. Methods We conducted three workshops with 13 co‐researchers from minority ethnic backgrounds. We explored perceptions and understanding of clinical trials alongside participatory art activities to help move away from verbocentric methods of communication. These artworks formed an exhibition that was presented to the community, prompting further discussions and engagement. Findings Co‐production workshops were an effective tool to introduce the public to trial research. With little knowledge of clinical trials at the beginning of the process, our co‐researchers formed a cohesive group, sharing initial fears and mistrust towards trials. As conversations progressed these attitudes clearly shifted. Artwork produced during the workshops was incorporated into an exhibition. Quotes and creative pieces from the group were included to reflect the themes identified. Presenting the exhibition at Riverside Festival enabled further engagement with a wider diverse community. The focus on co‐production helped build a network of individuals new to research and keen to become involved further. Conclusion Inclusive and democratic co‐production, enriched by participatory art practices, provided a powerful means of enabling our group to create new insights and foster new relationships. Projects like Talking Trials can diversify the research process itself-for example, four co‐researchers have commenced lay research partner roles on trial management groups and a lay advisory group is in development. Patient or Public Contribution Three members of staff at SRCDC were on the project delivery group and involved in the initial project design, subsequently helping to connect us with members of the Riverside community to work as co‐researchers. Two of the SRCDC staff are co‐authors of this manuscript. The project had 13 public co‐researchers guiding the direction of this research and creating the artwork displayed in the art exhibition.